Pemberdayaan Masyarakat berbasis Ekowisata (Studi Kasus Alih Fungsi Lahan Bengkok Menjadi Ekowisata “Taman Stambran” di Desa Tambangan Kec. Mijen Kota Semarang) - Hidayatullah, Ahmad (Jurnal at-Taghyir: Jurnal Dakwah dan Pengembangan Masyarakat Desa, 2022)
The orientation of the village community began to change from agrarian to industrial. resulting in decreased interest in the agrarian world - both agriculture and plantations - in rural communities, especially in areas close to the city, one of which is the village of Tambangan in Semarang. Therefore, changes in orientation also appear in crooked land management. Then the idea began to emerge to convert the crooked land into a more productive ecotourism area. This article uses a qualitative descriptive research method, and this article tries to explore community empowerment through ecotourism in Tambangan village. The results of this study indicate that the conversion of crooked land in RW 1 Tambangan can run smoothly without any internal conflicts. The presence of ecotourism in the region actually generates new ideas that have positive potential both socially and economically. The ecotourism concept applied by residents of RW 1 Tambangan is manifested in an integrative pattern between playing and learning in nature with the name “Taman Stambran” ecotourism. In addition, the positive impact on the economic sector is very meaningful for small traders who are native to the region. This positive result in the economic sector can be seen from the start of the establishment of small shops around tourist objects, without having to take up space for the conversion of crooked land that has been used to build and develop Stambran Park ecotourism. This is certainly very encouraging in the midst of the growing number of retailers.